Non-invasive diagnosis and monitoring tool of children’s mental health: A point-of-care immunosensor for IL-6 quantification in saliva samples - Cruz, Andrea; Vieira, Maria; Mesquita, Ana R.; Sampaio, Adriana; Mendes-Pinto, Inês; Soares, Isabel; Freitas, Paulo P. (Frontiers in Neuroscience, 2022)
Mental disorders are commonly featured as chronic conditions with often onset during childhood. In this context, inflammation has been associated with a higher risk of developing physical and mental health problems. Interleukin (IL)-6 is a key mediator of inflammatory responses and plays a pivotal role in immune and nervous system interaction. High levels of IL-6 during childhood are associated with mental problems, indicating that the IL-6 molecular pathway may represent a new target for monitoring and treating these conditions. Here, we report the detection of IL-6 in saliva samples from children (N = 118, mean age 4.4 years old) with behavioral problems using an immunosensor based on electrochemical impedance spectroscopy. This work demonstrates that the proposed immunosensor requires smaller sample volumes and is significantly faster and more sensitive than conventional ELISA while maintaining comparable levels of specificity and reproducibility. The point-of care immunosensor for detection of IL-6 in saliva samples presented herewith is, therefore, an attractive solution to the clinical practice as a rapid non-invasive, high-sensitive monitoring tool of mental health problems, especially in vulnerable patient populations such as children.